SIFAT FISIK MEKANIK PAPAN SERAT AMPAS TEBU BERDASARKAN JUMLAH LAPISAN DAN RASIO ASAM SITRAT-SUKROSA - Lestari, Yayuk; Setyawati, Dina; Nurhaida, Nurhaida (JURNAL HUTAN LESTARI, 2024)
Sugarcane bagasse fiber waste has not been utilized optimally. One of the uses of bagasse fiber waste is to make the waste into fiberboard. The research aim to evaluate the effect of the number of layers and the citric acid-sucrose ratio on the physical and mechanical properties of fiberboard and the best fiberboard that meets JIS A 5908:2003 Type 8 standards. The research was carried out in the wood processing laboratory of the Faculty of Forestry for + 4 months starting from the preparation of raw materials to testing and data processing. The experimental method used a factorial Completely Randomized Design (CRD) with two factors, namely the ratio of citric acid-sucrose (0/100, 25/75, 50/50, 75/25, 100/0) and the number of layers (one layer, three layers and five layers), each with three replicates. Fiberboard is made with dimensions of 30cm x 30cm x 1cm with a target density of 0,7 gr/cm3. The fiberboard is hot pressed at a temperature of 1800C for 10 minutes with a pressure of 35 kg/cm2. Based on research results, the ratio of citric acid to sucrose, the number of layers, and the interaction between the two have a significant effect on the physical and mechanical properties of fiberboard. The best fiberboard is found in the citric acid-sucrose ratio treatment of 75/25 with a single layer of board.Keywords: citric acid-sucrose, bagasse, fiberboard, number of layersAbstrakLimbah serat ampas tebu belum dimanfaatkan secara optimal. Salah satu pemanfaatan limbah serat ampas tebu adalah menjadikan limbah tersebut sebagai papan serat. Tujuan penelitian adalah mengevaluasi pengaruh jumlah lapisan dan rasio asam sitrat-sukrosa terhadap sifat fisik dan mekanik papan serat serta papan serat terbaik yang memenuhi standar JIS A 5908:2003 Type 8. Penelitian dilaksanakan di Laboratorium pengolahan kayu Fakultas Kehutanan selama + 4 bulan mulai dari persiapan bahan baku sampai pengujian dan pengolahan data. Metode percobaan menggunakan faktorial Rancangan Acak Lengkap (RAL) dengan dua faktor yaitu rasio asam sitrat-sukrosa (0/100, 25/75, 50/50, 75/25, 100/0) dan jumlah lapisan (satu lapis, tiga lapis dan lima lapis), masing-masing dengan tiga ulangan. Papan serat dibuat dengan ukuran 30cm x 30cm x 1cm dengan target kerapatan 0,7 gr/cm3. Papan serat dikempa panas pada suhu 1800C selama 10 menit dengan tekanan 35 kg/cm2. Berdasarkan hasil penelitian bahwa rasio asam sitrat-sukrosa, jumlah lapisan dan interaksi antara keduanya berpengaruh nyata terhadap sifat fisik dan mekanik papan serat. Papan serat terbaik terdapat pada perlakuan rasio asam sitrat-sukrosa 75/25 dengan jumlah lapisan satu lapis.Kata kunci: asam sitrat-sukrosa, ampas tebu, papan serat, jumlah lapisan